Studi Masalah Kesehatan Jiwa dengan Risiko Bunuh Diri pada Generasi Z di Kota Malang - Fatmawati, Rosida; Alfianto, Ahmad Guntur; Sulaksono, Ari Dwi (Universitas Batanghari Jambi, 2025)
The aim of this research is to illustrate the suicide risk among Generation Z in the city of Malang. The design used is quantitative with a survey approach. The population in this study is Generation Z, aged 19–26 years, in the city of Malang. The research sample consisted of 305 respondents using the Purposive Sampling technique. The research was conducted in 5 sub-districts, namely Lowokwaru, Sukun, Blimbing, Klojen, and Kedungkandang, from January to September 2024. The variable being studied is the risk of suicide. The measurement tool used is the Suicidal Ideation Scale (SIS) questionnaire. The SIS consists of 2 indicators: suicidal desire and resolved plans/preparations. Data analysis used the median and percentile values because the data is not normally distributed. The normality test was conducted using the Kolmogorov-Smirnov method with SPSS Statistics 27. The research results show that the desire to commit suicide has a median value of 2.00, suicide plans/preparations of 0.00, and an overall suicide risk of 3.0. The suicide risk among Generation Z in Malang City is 3.0, which means that the higher the mental health issues faced by Generation Z, the higher their suicidal thoughts.